Roof Inspection Using Drone at Melaka Islamic Museum - Khairi Supar; Sheikh Mohamad Naqib Sheikh Ismail; Muhammad Azammudin Azmi; Ariff Izzudin Jafri; Mohamad Azim Mohammad Azmi; Hairuddin Mohammad; Siti Khalijah Yaman (Multidisciplinary Applied Research and Innovation, 2024)
Heritage building abandonment is not a recent occurrence. Historical structures are frequently quite ancient and feature several structural flaws that may be noticed with the unaided eye or detected by experts. One of the most important aspects of a building’s upkeep is roof inspection. An examination of a building is mainly done to assess the roof’s condition. A constructed asset’s current status is difficult to ascertain without inspection, hence skipping inspection may increase the asset’s risk of failure in the future. The standard for property condition reports has been a longhand survey description. Because they satisfy the demand for the result of numerical analysis, surveys that utilize ratings rather than descriptions are becoming increasingly popular in the sector. In this study, we suggest a novel evaluation approach for evaluating the roof’s state and grading the seriousness of each found problem, derived from existing rating systems. The roof’s score, which is Condition Survey Protocol 1 (CSP1) Matrix, is then calculated by multiplying these two evaluation criteria. This matrix calls for brief explanations of the issues found rather than a detailed account of the roof’s flaws, which will cut down on the amount of time spent on site doing a roof inspection. The roof of Melaka Islamic Museum is given an overall grade of Good, Fair, or Dilapidated using the total score. Our general conclusions confirm the validity of the CSP1 Matrix.